Finance, extraction and logistics as axes of the third neoliberal moment in Latin America. (1st April 2019) - Peregalli, Alessandro
Abstract : With the notion of 'operations of capital', focused on the interaction between the dimensions of finance, extraction and logistics, authors such as Mezzadra and Neilson have highlighted some 'underlying transformations of capitalism' that go well beyond a generic idea of neoliberalism as 'the hegemonic circulation of economic doctrines or processes of deregulation and governance'. The aim of this article is to investigate the strong articulation of finance, extraction and logistics in Latin America by focusing on the creation of new infrastructural corridors in the continent during the 'third phase' of neoliberal hegemony in the region. This article brings together elements from the so-called 'critical logistics studies' literature with a range of other theoretical perspectives, including insights from the work of David Harvey, Giovanni Arrighi, Michel Foucault and Saskia Sassen. It applies this theoretical background to the Latin American reality, drawing on regional-specific literature and general data using a trans-disciplinary perspective.